2010
DOI: 10.1038/gt.2010.111
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy in the second eye of RPE65-deficient dogs improves retinal function

Abstract: The purpose of this study was to evaluate whether immune responses interfered with gene therapy rescue using subretinally delivered recombinant adeno-associated viral vector serotype 2 carrying the RPE65 cDNA gene driven by the human RPE65 promoter (rAAV2.hRPE65p.hRPE65) in the second eye of RPE65À/À dogs that had previously been treated in a similar manner in the other eye. Bilateral subretinal injection was performed in nine dogs with the second eye treated 85-180 days after the first. Electroretinography (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 36 publications
0
56
1
Order By: Relevance
“…However, unlike what was observed in the preclinical studies (Acland et al, 2001;Narfstrom et al, 2003;Le Meur et al, 2007;Annear et al, 2011), full-field Ganzfeld ERGs remained negligible in all treated LCA2 eyes. In two cases, the reduced nystagmus allowed the measurement of electrical responses from the treated area by the sensitive multifocal ERG technique (Maguire et al, 2009) (Table 1).…”
Section: Gene Therapy Clinical Trials For Lca2contrasting
confidence: 41%
See 1 more Smart Citation
“…However, unlike what was observed in the preclinical studies (Acland et al, 2001;Narfstrom et al, 2003;Le Meur et al, 2007;Annear et al, 2011), full-field Ganzfeld ERGs remained negligible in all treated LCA2 eyes. In two cases, the reduced nystagmus allowed the measurement of electrical responses from the treated area by the sensitive multifocal ERG technique (Maguire et al, 2009) (Table 1).…”
Section: Gene Therapy Clinical Trials For Lca2contrasting
confidence: 41%
“…This can be attributed to the features of the RPE (i.e., transducibility), the need for fine-regulated transgene expression in PRs, or the different rates of retinal degeneration, which is usually faster in PR-than RPE-specific diseases . To date, the most successful preclinical gene therapy study for a recessive RPE defect is represented by the AAV-mediated delivery of the 65-kDa RPE-specific isomerase (RPE65) in a dog model of LCA2 (Acland et al, 2001;Narfstrom et al, 2003;Le Meur et al, 2007;Annear et al, 2011), which has led to three independent human clinical trials in LCA2 patients, as discussed later. Gene replacement has been successfully evaluated in additional rodent models of IR caused by mutations in genes expressed in the RPE, such as MER tyrosine kinase (Mertk) (Vollrath et al, 2001;Smith et al, 2003;Tschernutter et al, 2005) and lecithin-retinol acyltransferase (LRAT) (Batten et al, 2005).…”
mentioning
confidence: 99%
“…Dogs were maintained initially in the dark for 3 days and then under a very dim light. ERGs were performed as previously described (Annear et al, 2011) except that an Espion e 2 visual electrophysiology system with ColorDome Ganzfeld (Diagnosys, Lowell, MA) was used and only a limited number of stimuli were tested following International Society for Clinical…”
Section: Electroretinography (Erg)mentioning
confidence: 99%
“…In addition, in one trial, despite observed visual improvement, the rate of progression of retinal degeneration in the vector-treated retina was reported to be similar to that in the contralateral untreated eye, 33 raising concerns about the longevity of the effects. Finally, unlike what was observed in LCA2 dogs, 25,[34][35][36] no improvement in the full-field electroretinogram has thus far been reported in LCA2 patients treated with AAV. Interspecies differences in either levels of RPE65 expression or AAV retinal transduction efficiency may explain this and suggest that there is room for improvement in LCA2 retinal gene therapy.…”
mentioning
confidence: 61%